Age-related changes in eggshell physical properties, ultrastructure, calcium metabolism-related serum indices, and gene expression in eggshell gland during eggshell formation in commercial laying ducks - Yanan Zhang (Elsevier, 2022)
ABSTRACT: This study evaluated the changes in eggshell mechanical properties, ultrastructure, calcium metabolism-related serum indices, and gene expression in eggshell gland during eggshell formation between laying ducks in the peak (young duck) and late phase (aged duck) of production. A total of 84 healthy young (31 wk of age) and 84 healthy aged (65 wk of age) Longyan laying ducks were each divided into 6 replicates of 14 birds, and caged individually. All the ducks were fed in one house with the same corn-soybean meal-based diet for 5 wk. The eggshell mechanical properties (shell proportion, thickness, breaking strength, and fracture toughness) and chemical components (matrix proteins, calcium, phosphorus, and magnesium) decreased in aged laying ducks (P < 0.05). Shell structural indices: total thickness, effective thickness and its proportion decreased, whereas mammillary knob width and its proportion increased (P < 0.05). The regulation values of early fusion, cuffing, caps, and total score of mammillary knobs were higher in aged laying ducks relative to the young ducks (P < 0.05). During the initial, growth and terminal stages of eggshell formation, shell thickness and breaking strength (terminal), shell weight, and its proportion (terminal) decreased in aged laying ducks (P < 0.05). Ultrastructural changes during shell formation indicated that the mammillary-knob density and effective thickness decreased (P < 0.05). Decreases occurred in serum content of phosphorus (growth), and estradiol and calcium contents (terminal) (P < 0.05). Relative expression of Ca2+ transporter and HCO3− exchanger, and matrix proteins genes decreased in aged laying ducks (P < 0.05) at all stages of eggshell formation. Collectively, the decreased incidence of early fusion and caps, increased thickness and width of mammillary knobs, and decreased effective thickness are the crucial differences leading to the compromised mechanical properties of eggshell in the late laying period. A disturbed regulation of calcium metabolism and uterine expression of ion transporters, especially for HCO3− exchange of aged laying ducks likely contribute to age-induced ultrastructural deterioration of the eggshell.